Klasterisasi Sumber Penyebaran Virus Covid-19 dengan Menggunakan Metode K-MEANS Di Daerah Kota Cimahi dan Kab. Bandung Barat - M. Reza Hidayat; Arief Rachman (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2020)
The Covid-19 virus originated from the city of Wuhan in China. Transmission is very fast and rapid to various parts of the world including Indonesia. This study discusses the clustering of sources of the spread of the covid-19 virus using the k-means method using software for Cimahi City and West Bandung Regency. The purpose of this study is to obtain information about 5 clusters of the source of the Covid-19 virus, namely cluster 0 (offices), cluster 1 (places to eat), cluster 2 (houses), cluster 3 (shopping), and cluster 4 (public transportation). during May to July 2020 for Cimahi City and West Bandung Regency. The results can be concluded that the highest cluster 0 from Kab. West Bandung with an average of 0,05%, for cluster 1 the highest impact of covid-19 was from Kab. West Bandung with an average of 0,55%, for cluster 2 with an average of 0,02%, for cluster 3 the highest impact of covid-19 was from Kab. West Bandung with an average of 0,04%, for cluster 4 the highest impact of covid-19 was from Cimahi City with an average of 0.79%.